Secure Quantum Key Distribution Encryption method for Efficient Data Communication in Wireless Body Area Sensor Net-works - Sai Suguna, Y; Kavya Reddy, B; Keerthi Durga, V; Roshini, A (International Journal of Engineering and Technology, 2018)
Wireless sensor networks has found its advancement in sensing the physiological parameters of human body through WBAN. Such nodes are either implanted or surface mounted on the human body in a particular position. The main purpose of these networks is to send the data generated by the wearable device outside the WLAN or the Internet. The BAN will continuously monitor the psychological changes like blood volume pressure (BVP), Brain signals etc. Uncertainty in the normal values will result in transmit all the information to the respective recipient to take required treatment. If an emergency is detected, the doctor instantly updates the patient’s health by sending a specific message. There is limited confidentiality, so the intruders will gather sensitive data. Public key cryptography can be used to create an unprotected communication channel. It also provides a convenient way to implement keys. This paper is focusing on a unique key generation technique called Quantum key distribution, which is used to create symmetric key method by using quantum properties of optics to transfer information from one Client to another in One-Time Pad manner. The special feature of the technique is to guarantee that the key cannot be intercepted during transmission without alerting the users to provide high authentication for received data.